Associations of advanced age with comorbidity, stage and primary subsite as contributors to mortality from colorectal cancer - Kazzem Gheybi; Kazzem Gheybi; Kazzem Gheybi; Elizabeth Buckley; Elizabeth Buckley; Agnes Vitry; David Roder; David Roder (Frontiers Media S.A., 2023)
BackgroundAlthough survival from colorectal cancer (CRC) has improved substantially in recent decades, people with advanced age still have a high likelihood of mortality from this disease. Nonetheless, few studies have investigated how cancer stage, subsite and comorbidities contribute collectively to poor prognosis of older people with CRC. Here, we decided to explore the association of age with mortality measures and how other variables influenced this association.MethodsUsing linkage of several administrative datasets, we investigated the risk of death among CRC cases during 2003-2014. Different models were used to explore the association of age with mortality measures and how other variables influenced this association.ResultsOur results indicated that people diagnosed at a young age and with lower comorbidity had a lower likelihood of all-cause and CRC-specific mortality. Aging had a greater association with mortality in early-stage CRC, and in rectal cancer, compared that seen with advanced-stage CRC and right colon cancer, respectively. Meanwhile, people with different levels of comorbidity were not significantly different in terms of their increased likelihood of mortality with advanced age. We also found that while most comorbidities were associated with all-cause mortality, only dementia [SHR = 1.43 (1.24-1.64)], Peptic ulcer disease [SHR = 1.12 (1.02-1.24)], kidney disease [SHR = 1.11 (1.04-1.20)] and liver disease [SHR = 1.65 (1.38-1.98)] were risk factors for CRC-specific mortality.ConclusionThis study showed that the positive association of advanced age with mortality in CRC depended on stage and subsite of the disease. We also found only a limited number of comorbidities to be associated with CRC-specific mortality. These novel findings implicate the need for more attention on factors that cause poor prognosis in older people.